2016
DOI: 10.1039/c6ob00132g
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies on intramolecular C–H trifluoromethoxylation of (hetero)arenes via OCF3-migration

Abstract: The one-pot two-step intramolecular aryl and heteroaryl C-H trifluoromethoxylation recently reported by our group has provided a general, scable, and operationally simple approach to access a wide range of unprecedented and valuable OCF3-containing building blocks. Herein we describe our investigations to elucidate its reaction mechanism. Experimental data indicates that the O-trifluoromethylation of N-(hetero)aryl-N-hydroxylamine derivatives is a radical process, whereas the OCF3-migration step proceeds via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 64 publications
2
12
0
2
Order By: Relevance
“…Stern–Volmer quenching experiments indicated that the deprotonated N ‐phenyl‐ N ‐hydroxylamide 2.1 ( E 1/2 red = +0.62 V vs. SCE) quenched *Ru(bpy) 3 2+ efficiently ( k q =7.84×10 9 m −1 s −1 ), while there was no observable quenching with the N ‐phenyl‐ N ‐hydroxylamide 2.2 and perfluoroisopropyl iodide ( 2.3 ; Scheme a). Furthermore, Ngai and co‐workers observed that the OR F migration was slower when electron‐deficient aromatic substrates were used, which was consistent with their previous observations and proposal of an ionic OR F ‐migration pathway . Based on this data, a reductive quenching photocatalytic cycle for selective O−R F bond formation and the subsequent OR F migration were proposed as outlined in Scheme b. Excitation of Ru(bpy) 3 2+ with visible light produces a long‐lived photoexcited *Ru(bpy) 3 2+ ( t 1/2 =1.10 μs), which is reductively quenched by 2.1 to give the N ‐hydroxyl radical 2.4 and Ru(bpy) 3 + .…”
Section: Synthesis Of Trifluoromethoxylated Compoundssupporting
confidence: 83%
“…Stern–Volmer quenching experiments indicated that the deprotonated N ‐phenyl‐ N ‐hydroxylamide 2.1 ( E 1/2 red = +0.62 V vs. SCE) quenched *Ru(bpy) 3 2+ efficiently ( k q =7.84×10 9 m −1 s −1 ), while there was no observable quenching with the N ‐phenyl‐ N ‐hydroxylamide 2.2 and perfluoroisopropyl iodide ( 2.3 ; Scheme a). Furthermore, Ngai and co‐workers observed that the OR F migration was slower when electron‐deficient aromatic substrates were used, which was consistent with their previous observations and proposal of an ionic OR F ‐migration pathway . Based on this data, a reductive quenching photocatalytic cycle for selective O−R F bond formation and the subsequent OR F migration were proposed as outlined in Scheme b. Excitation of Ru(bpy) 3 2+ with visible light produces a long‐lived photoexcited *Ru(bpy) 3 2+ ( t 1/2 =1.10 μs), which is reductively quenched by 2.1 to give the N ‐hydroxyl radical 2.4 and Ru(bpy) 3 + .…”
Section: Synthesis Of Trifluoromethoxylated Compoundssupporting
confidence: 83%
“…We also observed that the OR F migration is slower with more electron deficient aromatics, which is consistent with our previous observations and suggests an ionic OR F -migration pathway. 36 Based on these results, a detailed description of our proposed photocatalytic cycle for selective O–R F bond formation and the consequent OR F -migration is outlined in Fig. 2b .…”
Section: Resultsmentioning
confidence: 98%
“…Subsequent radical–radical coupling between Ib and ˙R F affords O -perfluoroalkylated N -phenyl- N -hydroxylamide Ic , which undergoes heterolytic N–OR F bond cleavage 47 , 48 followed by recombination of the resulting short-lived ion pair ( Id ) and then tautomerization to yield the final perfluoroalkoxylated arene product. 36 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[62] The OCF 3 migration step, however, is currently believed to proceed by heterolytic cleavage of the N À OCF 3 bond via formation of a nitrenium ion and a trifluoromethoxide anion.…”
Section: Methodsmentioning
confidence: 99%